Generation as a social variable. Issue 2 (3rd March 2020) - Mayall, Berry
ABSTRACT: In this short paper, I start with a case study – about how elementary school children in the early twentieth century in England understood their responsibilities vis-à-vis family (and school). This example provides a window into a past which deeply contrasts with present-day children's and adults' understandings and lives. I go on to consider (very briefly, for the field is vast) how ideas about childhood changed in the interwar years and how, since then, children have become locked into educational establishments – as well as into families. It seems to me that in these circumstances we are not used to thinking of children as thoughtful and active members of society. So it is no surprise to me that adults do not look to inter-relations with children as key variables towards understanding the social order. I note that my emphasis is on the UK, since I know most about that!